The Influence of Implementation Public Sector Accounting Accountability of Government at Agency Performance in Preventing Fraud - Gracia Lavenia Tampubolon; Renny Maisyarah (Sean Institute, 2025)
The implementation of public sector accounting plays a crucial role in enhancing transparency and accountability within government institutions. This study aims to analyze the impact of public sector accounting implementation on the performance of government institutions in preventing fraud. A quantitative research approach was employed, utilizing surveys and literature studies for data collection. The respondents consisted of financial officers and internal auditors from various government agencies. The findings indicate that the proper application of public sector accounting significantly contributes to improving institutional performance in detecting and preventing fraud. Key determinants of fraud prevention effectiveness include financial report transparency, internal supervision, and compliance with government accounting standards. Therefore, this study highlights the importance of implementing public sector accounting principles as a fundamental instrument in establishing clean governance and preventing corrupt practices.